The obstacles which are facing mathematics teachers in activating professional learning communities from their point of view - Mokli, Fahad Ibrahim; Zaylaee, Ahmed Abdullah (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the obstacles facing mathematics teachers in activating professional learning communities in Sabya's Educational directorate. The questionnaire was used in the study. which was consisting of three dimensions. (administrative obstacles, physical obstacles, and personal obstacles), the number of study sample members reached (716) teachers. the study found a set of obstacles, most notably: high number of classes given to the teacher, lack of training programs on professional learning communities, and teachers' low conviction in the process of change and development in their performance. The study also concluded that there were no statistically significant differences at the level (0.05) between the opinions of the sample members about the three dimensions of the study due to years of experience. The study recommended a number of recommendations.
Keywords: Obstacles; professional learning communities; mathematics teachers